2021
DOI: 10.1002/cnr2.1395
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cough in head and neck cancer patients at risk for dysphagia—An overview

Abstract: Background: This literature review explores the terminology, the neurophysiology, and the assessment of cough in general, in the framework of dysphagia and regarding head and neck cancer patients at risk for dysphagia. In the dysphagic population, cough is currently assessed perceptually during a clinical swallowing evaluation or aerodynamically.Recent findings: Recent findings have shown intra and inter-rater disagreements regarding perceptual scoring of cough. Also, aerodynamic measurements are impractical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
(288 reference statements)
0
4
0
Order By: Relevance
“…Moreover, our study population presented oral symptoms such as coughing and sticky saliva (items extracted from the EORTC QLQ-H&N35 questionnaire). These symptoms, added to the sensory deterioration due to oncological treatment may induce an inefficient cough reflex and thus increase the risk of dysphagia [ 29 ]. Consistent with our results, Nguyen and colleagues [ 30 ] found that only 40% of patients with HNC with dysphagia have an effective cough response to aspirated material, and, as described by Beetz and colleagues, [ 31 ] 43% of patients with HNC reported moderate to severe sticky saliva at 6 months after treatment with primary chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our study population presented oral symptoms such as coughing and sticky saliva (items extracted from the EORTC QLQ-H&N35 questionnaire). These symptoms, added to the sensory deterioration due to oncological treatment may induce an inefficient cough reflex and thus increase the risk of dysphagia [ 29 ]. Consistent with our results, Nguyen and colleagues [ 30 ] found that only 40% of patients with HNC with dysphagia have an effective cough response to aspirated material, and, as described by Beetz and colleagues, [ 31 ] 43% of patients with HNC reported moderate to severe sticky saliva at 6 months after treatment with primary chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the voluntary cough signals recorded by the two transducers showed that the skin-contact microphone underreports high-frequency components [49]. This observation may be explained by the attenuation of the acoustic signal propagating through the tissue of the neck before the signal is recorded by the skin-contact microphone, but also by the lack of the boosting of the high-frequency components (high-pass filtering) of the cough signal owing to the acoustic radiation at the lips.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in our previous overview [14], established cough assessment includes aerodynamic, acoustic measures, and perceptual ratings. While examining reflexive coughs induced with a tussigen, cough airflow-related measures are currently regarded as reliable markers of dysphagia and Extended author information available on the last page of the article aspiration in patients with neurological disorders [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, clinical examination of swallow is more frequently carried out by speech and language therapists. Clinical evaluation of oropharyngeal dysphagia often includes oral motor exam (Logemann et al., 1999), observation of coughing behaviour (Mootassim‐Billah et al., 2021) and sometimes palpation of laryngeal movement to detect aspiration (Felix et al., 2019). These procedures are relatively easy and simple to administer and are often used as the first line of assessment for oropharyngeal dysphagia.…”
Section: Introductionmentioning
confidence: 99%